From the bottom to the top: A more complete picture of the immigrant-native wage gap in Britain - Priscillia Hunt (IZA Journal of Migration, 2012)
This paper investigates wage assimilation of foreign-born male workers in Britain over the period 1993 to 2009. Using Labour Force Survey data, the paper employs a methodology (Blinder-Oaxaca quantile regressions) to decompose the immigrant-native wage differential at the mean and across the conditional wage distribution. Although immigrants earn more on average than natives, mean results mask that immigrants at the bottom (top) of the distribution earn less (more) than natives. Over the period investigated, the pro-UK-born unexplained component of the wage gap was greater at the bottom of the distribution and has shifted towards the centre of the distribution.
Keywords: J15; J16; J31; J71; 330; wage assimilation; decomposition; quantile regression; immigrant